Perceived Vulnerability to COVID-19 Infection and Psychosocial Well-Being of Nigerian Residents - Ogunsemi, Joshua Oludare; Akinnawo, Ebenezer Olutope; Akpunne, Bede Chinonye; Ariyo, Joy Osagiator (International Journal of Innovative Research in Medical Science, 2020)
The outbreak of the novel (SARS-CoV-2), known as COVID-19, has sparked global severe physical and mental health concerns in many spheres. Part of the identified mental health factors affecting people's psychosocial well-being is an increased level of health worries due to perception of vulnerability, which has been raised by excessive exposure to news, information on rising cases, mortality, and many others. This study focuses on the predictive influence of perceived vulnerability to COVID-19 infection among Nigeria residents during the COVID-19 outbreak. A total of 355 Nigerians, 175 (49.3%) males, 180 (50.7%) females aged between 18 years and 42 years (M = 27.24, SD =7.05) participated in the study through an online snowball method. Data was collected using the Perceived Vulnerability to Disease Questionnaire (PVDQ) and Mental Health Continuum Scale- Short Form (MHC-SF). Analysis of results reveals a high prevalence of low psychosocial well-being. That perceived vulnerability to COVID-19 infection significantly predicts psychosocial wellbeing (F (1,353) = 71.8, adj. R2 =.165, p <.01) among respondents. No significant sex influence was observed on psychosocial well-being; educational qualifications and marital status were found to influence the psychosocial well-being of Nigerian during COVID-19 Pandemic significantly. The authors conclude that perceived vulnerability to COVID-19 infection predicts the psychosocial well-being of Nigeria residents during the COVID-19 Pandemic outbreak.